6, 8-Diprenylorobol Induces Apoptosis in Human Hepatocellular Carcinoma Cells via Activation of FOXO3 and Inhibition of CYP2J2. (19th November 2020) - Lee, Chang Min; Lee, Jongsung; Jang, Su-Nyeong; Shon, Jong Cheol; Wu, Zhexue; Park, Kyungmoon; Liu, Kwang-Hyeon; Park, See-Hyoung
Abstract : 6, 8-Diprenylorobol is a phytochemical derived from the roots of Glycyrrhiza uralensis Fisch. 6, 8-Diprenylorobol exhibits several biological activities, but the effects of 6, 8-diprenylorobol on cancers have been hardly investigated. This study is aimed at elucidating the anticancer effect and working mechanism of 6, 8-diprenylorobol in HepG2 and Huh-7, two kinds of human hepatocellular carcinoma (HCC) cell lines. WST-1, cell counting, and colony formation assays and morphological change analysis showed that 6, 8-diprenylorobol treatment decreased the cell viability and proliferation rate. Cell cycle analysis indicated that 6, 8-diprenylorobol treatment increased the population of the G1/0 stage. Annexin V/PI double staining and TUNEL analysis showed that 6, 8-diprenylorobol treatment increased the apoptotic cell population and DNA fragmentation. Western blot analysis showed that 6, 8-diprenylorobol treatment increased the expression of cleaved PARP1, cleaved caspase-3, FOXO3, Bax, Bim, p21, and p27 but decreased the expression of Bcl2 and BclXL. Interestingly, 6, 8-diprenylorobol inhibited CYP2J2-mediated astemizole O -demethylation and ebastine hydroxylase activities with K i values of 9.46 and 2.61 μ M, respectively. CYP2J2 siRNA transfection enhanced the anticancer effect of 6, 8-diprenylorobol in HepG2 and Huh-7 cells through the downregulation of CYP2J2 protein expression and upregulation of FOXO3. Taken together, this study proposes that 6, 8-diprenylorobol treatment may be a useful therapeutic option against HCC by targeting CYP2J2 and FOXO3.